2014
DOI: 10.1016/j.numecd.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Dietary isoflavone intake is associated with evoked responses to inflammatory cardiometabolic stimuli and improved glucose homeostasis in healthy volunteers

Abstract: Background and Aims Consumption of foods that modulate inflammatory stress in genetically-prone individuals may influence development of cardiometabolic diseases. Isoflavones in soy-derived foods function as phytoestrogens, have antioxidant and anti-inflammatory activity, inhibit protein-tyrosine kinase activity, and may be atheroprotective. We examined the relationship between soy food consumption and inflammatory responses to endotoxemia, postprandial responses to oral lipid tolerance test (OLTT), and insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…The use of evoked endotoxemia (low-dose lipopolysaccharide) as a model of cardiometabolic disease is well documented [279][280][281][282] and has shown great utility as a discovery tool both in omic 283,284 and nutritional contexts. 88,285,286 The combination of nutritional and omic profiling in the context of evoked endotoxemia has great promise for understanding nutritional effects on inflammatory responses. Other challenges have also been successfully used in an integrative omic context, for example, the use of vaccination as a model for activation of immune response by Franco et al, 287 which revealed novel genes acting in response to immune activation.…”
Section: Evoked Phenotypesmentioning
confidence: 99%
“…The use of evoked endotoxemia (low-dose lipopolysaccharide) as a model of cardiometabolic disease is well documented [279][280][281][282] and has shown great utility as a discovery tool both in omic 283,284 and nutritional contexts. 88,285,286 The combination of nutritional and omic profiling in the context of evoked endotoxemia has great promise for understanding nutritional effects on inflammatory responses. Other challenges have also been successfully used in an integrative omic context, for example, the use of vaccination as a model for activation of immune response by Franco et al, 287 which revealed novel genes acting in response to immune activation.…”
Section: Evoked Phenotypesmentioning
confidence: 99%
“…Notably, the anti-inflammatory properties of omega-3 polyunsaturated fatty acids have been assessed by administering fish oil either parenterally 126 or through dietary supplementation 125, 127 prior to the endotoxin challenge, while habitual dietary intake of soy-derived foods may also modify the response to endotoxemia. 128 …”
Section: Evidence For Translation and Clinical Relevancementioning
confidence: 99%
“…Furthermore, there was protection on induced inflammation by decline of insulin resistance, and better response to oral glucose tolerance test [31].…”
Section: Soybean and Metabolic Effectsmentioning
confidence: 94%
“…Ferguson et al [31] evaluated the relationship between consumption of foods containing isoflavones on the inflammatory response caused by the transient endotoxemia, noticing an increase of the immune response related to the consumption of isoflavones. Furthermore, there was protection on induced inflammation by decline of insulin resistance, and better response to oral glucose tolerance test [31].…”
Section: Soybean and Metabolic Effectsmentioning
confidence: 99%
See 1 more Smart Citation